Bridging the Gap, Creating Equity through Wisdom: The Sustainable Development of Inclusive Preschool Education in the Era of Artificial Intelligence - Huiying, Jiang (INTI International University, 2025)
Artificial intelligence (AI) significantly advances sustainable inclusive early childhood education through three interconnected pathways: (1) personalized learning enabling equitable development foundations; (2) resilient safety systems via real-time monitoring; and (3) enhanced home-school collaboration through data-driven communication. These innovations collectively optimize teacher effectiveness and foster socio-emotional skills. However, critical challenges threaten system sustainability: data privacy risks, disparities in teachers' AI competencies, and the widening "intelligence gap" exacerbating inequities. To address these barriers, human-centered strategies are imperative: establishing robust data governance frameworks, promoting lifelong teacher professional development, and bridging the intelligence divided through policy-technology synergy. Only through such integrated approaches can inclusive early education achieve its goals of quality, equity, and sustainability aligned with global commitments (SDG 4, SDG 9c.).